2004
DOI: 10.1023/b:neon.0000021900.29176.58
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Neurocognitive Outcome in Adult Brain Tumor Patients

Abstract: Primary malignant brain disease was found to be less negative on neurocognitive outcomes for younger than for either middle-aged or older patients. Treatments were not as predictive of neurocognitive outcomes as age. No single test outcome measure was as sensitive to neurocognitive status as the empirically derived index of attention and concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…Age was one of the strongest determinants of cognitive outcome in a series of 79 primary brain tumour patients assessed at UCLA (Kaleita et al . ). In this study, authors showed that the strongest predictor of performance on neurocognitive test was age.…”
Section: Methodsmentioning
confidence: 97%
“…Age was one of the strongest determinants of cognitive outcome in a series of 79 primary brain tumour patients assessed at UCLA (Kaleita et al . ). In this study, authors showed that the strongest predictor of performance on neurocognitive test was age.…”
Section: Methodsmentioning
confidence: 97%
“…We utilized a multiple cutoff approach such that better‐performing survivors needed to score no more than 1.5 SD below the mean on all selected measures to minimize the likelihood that group membership was attained by chance alone on a single measure. Lastly, our sample size was somewhat larger than other studies examining cognitive functioning in brain tumor survivors …”
Section: Discussionmentioning
confidence: 98%
“…Lastly, our sample size was somewhat larger than other studies examining cognitive functioning in brain tumor survivors. 11,12,28,[37][38][39]…”
Section: Study Limitationsmentioning
confidence: 99%
“…(3) Has there been cognitive decline secondary to tumor recurrence (Bosma et al 2007;Glosser et al 1997)? (4) Does the rehabilitation program or any of its components improve (or affect) cognitive functioning (Kaleita et al 2004;Langer et al 2002;Mabbott et al 2008;Mehta et al 2003;Meyers et al 2004)? (5) Can survival rates be predicted using estimates of baseline cognitive functioning (Armstrong et al 2003;Meyers et al 2000)?…”
Section: Multiple Concussionsmentioning
confidence: 99%